2014
DOI: 10.1186/s12935-014-0074-z
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting CCN1 blocks AML cell growth by disrupting the MEK/ERK pathway

Abstract: BackgroundCCN1 plays distinct roles in various tumor types, but little is known regarding the role of CCN1 in leukemia.MethodsWe analyzed CCN1 protein expression in leukemia cell lines and in AML bone marrow samples. We also evaluated the effects of antibody- or siRNA-mediated inhibition of CCN1 on the growth of two AML cell lines (U937 and Kasumi-1 cells) and on the MEK/ERK pathway, β-catenin and other related genes.ResultsU937 and Kasumi-1 cells had markedly higher CCN1 expression than the 5 other leukemia c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 49 publications
2
26
2
Order By: Relevance
“…It was recently reported that the level of Cyr61 is increased in BM supernatants from patients with ALL, and this change could promote ALL cell survival (22). Previous studies showed that BM stromal cells are the major source of Cyr61 (21,32). Our current study showed that Cyr61 was overexpressed not only in the BMMNCs from patients with ALL, but also two ALL cell lines.…”
Section: Discussionsupporting
confidence: 57%
“…It was recently reported that the level of Cyr61 is increased in BM supernatants from patients with ALL, and this change could promote ALL cell survival (22). Previous studies showed that BM stromal cells are the major source of Cyr61 (21,32). Our current study showed that Cyr61 was overexpressed not only in the BMMNCs from patients with ALL, but also two ALL cell lines.…”
Section: Discussionsupporting
confidence: 57%
“…CYR61 is a connective tissue growth factor which has been considered as a crucial mediator in the developing and metastasis of cancers [26]. High expression of CYR61 was present in cervical cancer [27] and oesophageal squamous cell carcinoma [28], and exerted diverse functions in several types of cancers [29]. In malignant melanoma, CYR61 worked as a biomarker for tumour cells proliferation and metastasis, making it a potential target for melanoma treatment [30].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the NF‐κB pathway contributed to the anti‐apoptotic function of Cyr61. Recent evidence suggests that Cyr61 mediates ALL and AML cell survival by the AKT pathway and by the ERK1/2 pathway, respectively; however, we found that AKT and ERK1/2 were not involved in the ability of Cyr61 to inhibit the apoptosis of CML cells induced by IM. Further analysis showed that Cyr61 treatment led to strong activation of NF‐κB signaling as well as Bcl‐2 production.…”
Section: Discussioncontrasting
confidence: 85%